Raising and Maintaing the Market Presence of XYZ - Jessica Jessica; Clarissa Nathania (iBuss Management, 2014)
With the recent issue, from being only a supporting office to a partner of ABC, that forced XYZ to transform its role and to expand its function. XYZ shall no longer depend on the funds given by other countries; instead they must seek aids from their local citizens. This issue results in the necessities of XYZ to make their mission and ideas known to public. One of the ways to do so is through delivering an effective content marketing in order to gain the brand awareness. Thus, this research aims to find the most effective content marketing that contributes the highest level of convincement to raise their awareness, by analyzing the responses gathered from 100 respondents using the ordinal regression method. The 100 respondents are sampled using the stratified sampling method. This research found that infographics is the most effective content marketing, the writers also provide the most desired feedbacks by donators in order to maintain their loyalty which is the display of improvement of the people. Keywords: Non-Profit Organization, Content Marketing, Brand Awareness, and Feedbacks